Distribution of Pt single atom coordination environments on anatase TiO2 supports controls reactivity - Wenjie Zang; Jaeha Lee; Peter Tieu; Xingxu Yan; George W. Graham; Ich C. Tran; Peikui Wang; Phillip Christopher; Xiaoqing Pan (Nature Communications, 2024)
Abstract Single-atom catalysts (SACs) offer efficient metal utilization and distinct reactivity compared to supported metal nanoparticles. Structure-function relationships for SACs often assume that active sites have uniform coordination environments at particular binding sites on support surfaces. Here, we investigate the distribution of coordination environments of Pt SAs dispersed on shape-controlled anatase TiO2 supports specifically exposing (001) and (101) surfaces. Pt SAs on (101) are found on the surface, consistent with existing structural models, whereas those on (001) are beneath the surface after calcination. Pt SAs under (001) surfaces exhibit lower reactivity for CO oxidation than those on (101) surfaces due to their limited accessibility to gas phase species. Pt SAs deposited on commercial-TiO2 are found both at the surface and in the bulk, posing challenges to structure-function relationship development. This study highlights heterogeneity in SA coordination environments on oxide supports, emphasizing a previously overlooked consideration in the design of SACs.